Lost in a haystack: The importance of physical re-examination - Dheeraj Jain; Stalin Viswanathan; Jagatheeswari Shanmugam (Elsevier, 2014)
Summary: We report an unusual case of varicella zoster in a 19-year-old, who presented with persisting fever even after her lesions began forming scabs. Fever workup for secondary complications was negative. A re-examination revealed an axillary eschar. She recovered completely with doxycycline. This report suggests the importance of keeping in mind, epidemiological data of common diseases in the locality, as well as the significance of a thorough physical examination in patients with fever. Keywords: Scrub typhus co-infection, Rickettsial rash, Varicella zoster